Forensic Pharmacy Case Study: Identification of Hazardous Mercury Content as a Whitening Agent in Beauty Cream Products - Ardianto, Nanda; Prasetyawan, Fendy; Saristiana, Yuneka; Muslikh, Faisal Akhmal; Mildawati, Ratna; Dhafin, Anis Akhwan; Arifin, Candra; Rofiq, Abd (PT FORMOSA CENDEKIA GLOBAL, 2023)
Forensic pharmacy is crucial in identifying hazardous substances like mercury in beauty products. Counterfeit items with mercury pose health risks, emphasizing the need for accurate identification methods. The research, employing content analysis, focuses on illegal cosmetics containing mercury, aiming to understand distribution patterns and assess associated health risks. This systematic approach provides valuable insights into public health issues, contributing to safer regulatory practices. The utilization of these products may pose serious health risks to consumers. The implicated products include Temulawak New Day & Night, CAC Glow, Natural 99, HN (Day & Night), SP Special UV Whitening, Dr Original Pemutih, Super DR Quality Gold SPF 30, Diamond Cream, Herbal Plus New Day & Night, Ling Zhi Day & Night, Sj Sin Jung, Tabita, and Krim Labella. In Indonesia, the use of mercury in cosmetic products is prohibited by legislation, such as Law Number 32 of 2009 on Environmental Protection and Government Regulation of the Republic of Indonesia Number 81 of 2016 on the Security of Industrial Chemicals. Additionally, BPOM, responsible for overseeing drugs, food, and cosmetics, has issued relevant regulations